Tubulointerstitial nephritis and uveitis. Issue 6 (November 2017) - Pakzad-Vaezi, Kaivon; Pepple, Kathryn L.
Abstract : Purpose of review: Tubulointerstitial nephritis and uveitis (TINU) is an important yet underrecognized ocular inflammatory syndrome. This review summarizes key historical publications that identified and defined the syndrome, and more recent literature that reveal the importance of urinary β2-microglobulin testing and kidney biopsy in the diagnostic evaluation of patients with TINU. Additionally, research studies providing new insights into disease pathogenesis are highlighted. Recent findings: In contrast with initial reports of TINU manifesting exclusively as an anterior uveitis in pediatric patients, more recent reports have identified TINU in patients of all ages with a wide range of ocular manifestations. Urinary β2-microglobulin has emerged as a sensitive and specific laboratory screening test, and the role of kidney biopsy in differentiating TINU from sarcoidosis continues to evolve. Genetic studies have identified HLA-DQA1 * 01, HLA-DQB1 * 05, and HLA-DRB1 * 01 as high-risk alleles and the identification of antimonomeric C-reactive protein antibodies suggests a role for humoral immunity in disease pathogenesis. Management strategies have evolved to include systemic anti-inflammatory treatment as a result of important outcome studies in patients with significant renal and ocular disease. Summary: With greater recognition, understanding, and treatment of this syndrome, both ocular inflammation and renal disease can be better addressed.